Incentive Compatibility in Signaling Games with a Continuum of Types - Mailath, George J. (Econometrica, 1987)
This paper provides two results that are useful in proving the exist ence of and characterizing separating equilibria in signaling games. A key element in the analysis of separating equilibria is the examina tion of the implied incentive compatibility constraints. It is shown that these constraints imply differentiability of strategies. In addi tion, a monotonicity condition (which is similar to the single crossi ng condition) is analyzed that is necessary and sufficient for there to be a strategy satisfying the incentive compatibility constraints. As a direct consequence of these two results, the analysis of Paul Milgrom and John Roberts (1982) is considerably strengthened. Copyright 1987 by The Econometric Society.